2021
DOI: 10.1177/02537176211005017
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic and Stepped Care Model for Perinatal Depression in Rural India: Lessons Learned and the Way Forward

Abstract: which often leads to further widening of the treatment gap for CMDs during and after such conditions. 7,8 To reduce the treatment gap for CMDs, the government of India has taken initiatives such as an increase in the number of training institutes for psychiatry and allied courses and also postgraduate seats. 5,9 Besides, the stepped care models may be used to improve the delivery of mental health services in the rural and inaccessible regions, with a primary focus on cost-effectiveness, accessibility, and sust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…For example, in some Indian regions, like Kashmir, the implementation of digital psychiatry in mental health service infrastructures may be challenging due to the second generation (2G) mobile network, frequent communication blackouts, poor digital literacy, and absence of a skilled, adequately educated and sufficient mental health workforce able to encounter the burden of Indian mental diseases (Shoib & Arafat, 2021). Therefore, in the Indian sample there is a great disparity in terms of Internet and digital tools access, as already reported in previous studies (Andersson et al, 2019; Firth et al, 2019; Ransing et al, 2021; Shoib & Yasir Arafat, 2020b). Moreover, most of the sample recruited by Nepal coming from Kathmandu city, which represents the capital of the country and one of the biggest and digitalized city of Nepal, being the city with more Internet access and connectivity as well as with more available digital psychiatry platforms (commercial; Singh et al, 2021).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…For example, in some Indian regions, like Kashmir, the implementation of digital psychiatry in mental health service infrastructures may be challenging due to the second generation (2G) mobile network, frequent communication blackouts, poor digital literacy, and absence of a skilled, adequately educated and sufficient mental health workforce able to encounter the burden of Indian mental diseases (Shoib & Arafat, 2021). Therefore, in the Indian sample there is a great disparity in terms of Internet and digital tools access, as already reported in previous studies (Andersson et al, 2019; Firth et al, 2019; Ransing et al, 2021; Shoib & Yasir Arafat, 2020b). Moreover, most of the sample recruited by Nepal coming from Kathmandu city, which represents the capital of the country and one of the biggest and digitalized city of Nepal, being the city with more Internet access and connectivity as well as with more available digital psychiatry platforms (commercial; Singh et al, 2021).…”
Section: Discussionsupporting
confidence: 50%
“…For example, in some Indian regions, like Kashmir, the implementation of digital psychiatry in mental health service infrastructures may be challenging due to the second generation (2G) mobile network, frequent communication blackouts, poor digital literacy, and absence of a skilled, adequately educated and sufficient mental health workforce able to encounter the burden of Indian mental diseases (Shoib & Arafat, 2021). Therefore, in the Indian sample there is a great disparity in terms of Internet and digital tools access, as already reported in previous studies (Andersson et al, 2019;Firth et al, 2019;Ransing et al, 2021;Shoib & Yasir Arafat, 2020b (Apaydin et al, 2018;Feijt et al, 2020;Gibson et al, 2011;Turvey et al, 2013;Wells et al, 2018;Wright et al, 2019). Moreover, regarding the COVID-19 pandemic, most of the sample declared that digital psychiatry may potentially allow clinicians to ensure continuity of care in times of COVID-19-related emergencies, as already reported in other studies, particularly for more vulnerable and physically proven individuals, such as elderly (Chen et al, 2020;Feijt et al, 2020;Ghebreyesus, 2020;Hilty et al, 2013;Jameson et al, 2011;Wagnild et al, 2006).…”
Section: Level Of Knowledgementioning
confidence: 89%
“…The CCPP focuses on developing and implementing the primary HCWs -based care for CVH. Primary HCW-based models have been found to be effective in many LMIC countries for several other health conditions related service delivery, including COVID-19 pandemic times (13)(14)(15). Primary HCWs (e.g., Accredited Social Health Activist) are pillars of several national programs, service delivery by them is more acceptable and is better integrated with general healthcare infrastructure.…”
Section: Human Resourcesmentioning
confidence: 99%
“…However, a previous study from the same rural setting found that perinatal women had limited access to phones, the internet, and social media. 11 To summarize, most vaccinated perinatal women were unwilling for COVID-19 vaccination, and their concerns about COVID-19 vaccines remained unaddressed. Therefore, there is an urgent need to develop and implement a feasible and acceptable individual-level intervention to address these concerns.…”
Section: A Pilot Exploration Of the Experiences Of Covid-19 Vaccinate...mentioning
confidence: 99%
“…However, a previous study from the same rural setting found that perinatal women had limited access to phones, the internet, and social media. 11 …”
mentioning
confidence: 99%